Drug Repositioning for Preeclampsia Therapeutics by In Vitro Screening: Phosphodiesterase-5 Inhibitor Vardenafil Restores Endothelial Dysfunction via Induction of Placental Growth Factor. (October 2015) - Kakigano, Aiko; Tomimatsu, Takuji; Mimura, Kazuya; Kanayama, Tomoko; Fujita, Satoko; Minato, Kenji; Kumasawa, Keiichi; Taniguchi, Yukiko; Kanagawa, Takeshi; Endo, Masayuki; Ishihara, Tomoaki; Namba, Takushi; et al.
We screened a library of 528 approved drugs to identify candidate compounds with therapeutic potential as preeclampsia treatments via their proangiogenic properties. Using human umbilical vein endothelial cells (HUVECs), we assessed whether the screened drugs induced placental growth factor (PIGF) and restored damaged endothelial cell function. Enzyme-linked immunosorbent assays (ELISAs) were carried out to measure levels of PlGF in conditioned media treated with each drug (100 µmol/L) in the drug library. Tube formation assays were performed using HUVECs to evaluate the angiogenic effects of drugs that induced PlGF. We also performed ELISA, quantitative reverse transcription polymerase chain reaction, and tube formation assays after treatment with a range of concentrations of the candidate drug. Of the drugs that induced PlGF, vardenafil was the only compound that significantly facilitated tube formation in comparison with the control cells ( P < .01). Treatment with vardenafil at concentrations of 50, 100, and 250 µmol/L increased expression of PlGF in a dose-dependent manner. Vardenafil (250 µmol/L) significantly improved tube formation which was inhibited in the presence of soluble fms-like tyrosine kinase 1 (100 ng/mL) and/or soluble endoglin (100 ng/mL). Production of PlGF from HUVECs in the presence of sera derived from patients with preeclampsia was significantly elevated by administration of vardenafil (250 µmol/L). By assessing drug repositioning through screening a library of approved drugs, we identified vardenafil as a potential protective agent against preeclampsia. The therapeutic mechanism of vardenafil may involve inhibition of the systemic maternal antiangiogenic state that leads to preeclampsia, in addition to its vasodilating effect. As concentrations used are high and unlikely to be useful clinically, further work is needed before testing it in humans.